RANCANGAN SISTEM INFORMASI PENCATATAN KARCIS MASUK DAN KOLEKSI PADA MUSEUM SIGINJAI JAMBI - Susanto, Darex; Marianto, Doni (LP2M Universitas Nurdin Hamzah, 2024)
Abstract – The Information System for Recording Entry Tickets and Collections at the Siginjai Jambi Museum is a solution to overcome the obstacles of the manual approach that is still applied by museums in managing entrance tickets and recording collections. This research aims to evaluate operational efficiency and analyze the maintenance and documentation of museum collections. The background to the report highlights the need for museums to adapt to developments in information technology to ensure their sustainability and relevance in presenting information to the public. The Siginjai Jambi Museum, as a cultural heritage preservation institution, still faces challenges in managing and presenting information using manual methods.